Centro de cohesión social y resignificación del legado cultural en Úmbita, Boyacá (2022)
This article is based on the approach of an architectural equipment in the municipality of Úmbita, belonging to the department of Boyacá, this, being a rural sector, is constantly affected by the territorial inequality suffered by rural areas in confrontation to urban areas, in the latter is where facilities and services are concentrated to a greater extent; which gives space to social segregation. Over the years this gap has been increasing and has led to disconnected areas with marginalization and vulnerability, these problems seek to be solved from participatory architecture, which is defined by a social work that bases its existence on: the architect-community relationship, based on the need to generate habitat alternatives based on a democratization of design processes.